Ophiopogon ximengensis, a new species from Yunnan, Southern China - Hao, Jia-Chen; Feng, Hui-Zhe; Tan, Kun; Liu, Li-An; Lin, Qin-Wen (Phytotaxa, 2025)
Ophiopogon ximengensis, a newly described species from Yunnan Province, SW China, is illustrated herein. Characterized by its strongly recurved tepals O. ximengensis resembles O. griffithii originally described from the same region. However, it is distinctly identifiable by its shorter and broader, more distinctly inequilateral leaf blades, denser inflorescences usually with a tuft of 2 or 3 clustered flowers in axils of bracts and shorter internodes, and more strongly recurved, internally unspotted white perianth lobes. Additionally, we provide notes on its habitat, conservation status, phenology, and taxonomic relationships with related species.